PEMBENTUKAN KARAKTER ISLAMI MELALUI PEMBIASAAN JUMAT TAKWA SISWA DI SDN 5 KOMET BANJARBARU - Nurhidayani Yeni; ulfah, Aunia Ulfah; Yonisa, Tri Yonisa; Fitriani Aspahani (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
This study explores the role of religious upbringing in shaping Islamic character among students in schools.By examining the integration of religious practices into daily routines , the study aims to understand how consistent exposure to religious teachings influences the development of Islamic values and behaviour . Through a comparative analysis of educational approaches in Indonesia, this research investigates the methods employed to instill religious values within the school environment. Findings suggest that a combination of curriculum content,extracurricular activities, and teacher-student interactions significantly contribute to the cultivation of Islamic character. The study underscores the importance of incorporating religious teachings into educational frameworks to foster a strong foundation of Islamic ethics and morality among students.